2017
DOI: 10.1177/2151458517696680
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury in the Geriatric Population: Risk Factors, Treatment Options, and Long-Term Management

Abstract: Spinal cord injuries (SCIs) are sustained by more than 12 500 patients per year in the United States and more globally. The SCIs disproportionately affect the elderly, especially men. Approximately 60% of these injuries are sustained traumatically through falls, but nontraumatic causes including infections, tumors, and medication-related epidural bleeding have also been documented. Preexisting conditions such as ankylosing spondylitis and diffuse idiopathic skeletal hyperostosis can render the spine stiff and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
(52 reference statements)
4
30
0
Order By: Relevance
“…23,25 Knowing that this clinical course is not unusual for elderly patients after tSCI, and given their frailty and limited functional and neurological recovery, clinicians are increasingly faced with the challenge of weighing the risks and anticipated potential benefits of surgery. 26 A further challenge is the limited evidence and tools available to facilitate the discussion and education about prognosis with patients and their families making difficult decisions regarding goals of management in severely injured elderly patients. 27 Few studies focus on in-hospital mortality of the elderly population, with fewer comparing this outcome following surgical and non-surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…23,25 Knowing that this clinical course is not unusual for elderly patients after tSCI, and given their frailty and limited functional and neurological recovery, clinicians are increasingly faced with the challenge of weighing the risks and anticipated potential benefits of surgery. 26 A further challenge is the limited evidence and tools available to facilitate the discussion and education about prognosis with patients and their families making difficult decisions regarding goals of management in severely injured elderly patients. 27 Few studies focus on in-hospital mortality of the elderly population, with fewer comparing this outcome following surgical and non-surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, there has been a shift in the mean age at SCI from 26 years old to 38 years old, 4 resulting in an increasingly large proportion of elderly SCI patients. 20,37 The percentage of traumatic SCI patients over 60 years of age has increased from 4.6% in the 1970s to 13.2% in the 2000s. 11 Past studies have shown that older patients, as compared to younger patients, have a higher rate of complications and death after SCI and are less likely to be independent in self-care at discharge.…”
mentioning
confidence: 99%
“…SCI is an umbrella term, encompassing numerous pathologies and presentations with varying etiologies. While 96% of all SCI cases result from trauma, nontraumatic SCIs are more prevalent in the elderly population and can be observed resulting from tumors, vascular disease, degenerative disease, inflammation, and other etiologies [ 2 , 9 ]. It is worth mentioning that natural, age-related physiological changes lead to a higher likelihood of cervical fractures and SCIs.…”
Section: Discussionmentioning
confidence: 99%
“…The elderly population is more likely to experience diseases affecting bone integrity, including osteoporosis and osteopenia, placing them at higher risk of injury [ 2 ]. Degenerative changes of the spine are seen in 90% of men over 50 years old and 90% of women over 60 years old, which may lead to spondylosis and increase the prospect of SCIs, fractures, and spinal stenosis [ 2 , 9 ]. One potential nontraumatic etiology of SCI is pannus, an accumulation of granulation tissue leading to subsequent erosion of subchondral bone and resultant decrease of bone strength.…”
Section: Discussionmentioning
confidence: 99%